The evolution of diagnosis of polymyalgia rheumatica - A. M. Satybaldyev (Научно-практическая ревматология, 2019)
The paper considers the evolution of knowledge of polymyalgia rheumatica (PR) since 1888 and presents dynamics in the creation of a unified terminology. It characterizes the diagnostic development process, by using the criteria by H.A. Bird et al. 1979, J.G. Jones and B.L. Hazleman 1981 (UK), T.Y. Chuang, G.G. Hunder et al. 1982 (USA), M. Nabunaga et al. 1989 (Japan), and L.A. Healey 1984 (USA) as an example. The author scrutinizes the validation of these criteria in different countries and then the process of developing international classification criteria for PR (under the auspices of the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR), by validating the new classification and previously existing diagnostic criteria.